2009
DOI: 10.1163/187666309x12491131130468
|View full text |Cite
|
Sign up to set email alerts
|

When Do Universal Preferences Emerge in Language Development? The Acquisition of Hebrew Stress

Abstract: When children have to select one of two structures, do they start with the universally unmarked structure or with the one preferred by the ambient language? Th is question is directly relevant to metrical systems, which often employ either iambs or the universally unmarked trochees. We argue that children start with the universally unmarked trochaic foot, unless their ambient language provides them with suffi cient data to arrive at the language-specifi c preferred foot prior to the onset of speech. We show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…The course of oral language development itself, which is, as we have seen, closely linked to gestural development, can vary greatly depending on the language being learned. Such language‐specific effects on learning are found for early phonological processing and lexical–prosodic processing influencing vocabulary growth (see Adam & Bat‐El, ; Bleses et al., ; Bouchon, Floccia, Fux, Adda‐Decker, & Nazzi, ; Delle Luche, Floccia, Granjon, & Nazzi, ; Höhle, Bijeljac‐Babic, Herold, Weissenborn, & Nazzi, ; Nazzi, Floccia, Moquet, & Butler, ; Thordardottir, ). In the aforementioned context, it is difficult to conclude whether differences in gestural use observed in crosscultural studies (e.g., Iverson et al., ) are due to cultural environments (such as a rich gestural model from adults, for example), or differences in language growth, which then cascade onto differences in gestural development.…”
Section: Background Literaturementioning
confidence: 98%
“…The course of oral language development itself, which is, as we have seen, closely linked to gestural development, can vary greatly depending on the language being learned. Such language‐specific effects on learning are found for early phonological processing and lexical–prosodic processing influencing vocabulary growth (see Adam & Bat‐El, ; Bleses et al., ; Bouchon, Floccia, Fux, Adda‐Decker, & Nazzi, ; Delle Luche, Floccia, Granjon, & Nazzi, ; Höhle, Bijeljac‐Babic, Herold, Weissenborn, & Nazzi, ; Nazzi, Floccia, Moquet, & Butler, ; Thordardottir, ). In the aforementioned context, it is difficult to conclude whether differences in gestural use observed in crosscultural studies (e.g., Iverson et al., ) are due to cultural environments (such as a rich gestural model from adults, for example), or differences in language growth, which then cascade onto differences in gestural development.…”
Section: Background Literaturementioning
confidence: 98%
“…There is growing evidence that, according to the language they acquire, monolinguals' learning paths can differ, including for early lexical prosodic processing (Adam & Bat-El, 2009), word segmentation (across dialects: Nazzi, Mersad, Sundara, Iakimova, & Polka, 2014), and phonological processing (Nazzi, Floccia, Moquet, & Butler, 2009;Mani & Plunkett, 2007;Delle Luche, Floccia, Granjon, & Nazzi, 2016;Bouchon, Floccia, Fux, Adda-Decker, & Nazzi, 2015), culminating in differences in vocabulary growth (Bleses et al, 2008;Thordardottir, 2005). Bilingualism is likely to exacerbate these languagespecific differences, adding not only a new language but also the complexity of interactions between languages.…”
Section: Study 1: Understanding the Role Of Linguistic Distance In Bimentioning
confidence: 99%
“…Although the question of whether infants' initial biases for a certain stress pattern is universal is not central to this study, it is important to note that contradictory evidence has been found in this topic. See Rose and Champoizea (2007) and Adam and Bat-El (2007) for further discussion on the subject.…”
mentioning
confidence: 99%